2018
DOI: 10.1148/radiol.2017170760
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Evaluation of Vertebral Microvascular Permeability and Fat Fraction in Alloxan-induced Diabetic Rabbits

Abstract: Purpose To determine longitudinal relationships between lumbar vertebral bone marrow permeability and marrow adipose tissue in a rabbit diabetes model by using quantitative dynamic contrast agent-enhanced (DCE) magnetic resonance (MR) imaging and iterative decomposition of water and fat with the echo asymmetry and least-squares estimation quantitation (IDEAL IQ) sequence. Materials and Methods Twenty rabbits were randomly assigned to the diabetic (n = 10) or control (n = 10) group. All rabbits underwent sagitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 28 publications
4
27
0
Order By: Relevance
“…Prior studies have shown that biopsy is difficult and many complications are involved in assessment of diabetic pancreatic pathology; such studies often involve the use of human organ donor tissue samples [24, 25] or the establishment of animal models [26, 27]. Hu et al found that the IDEAL IQ sequence can be used for quantitative evaluation of vertebral fat deposition in alloxan-induced diabetic rabbits; however, changes in PFC remain unclear in the context of diabetic rabbits [28]. Importantly, unlike previous MRI techniques used to evaluate visceral fat, the IDEAL-IQ enables adjustment for common biases in the measurement of tissue fat, including T 1 and T 2 * effects, as well as main magnetic field inhomogeneity [29, 30].…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have shown that biopsy is difficult and many complications are involved in assessment of diabetic pancreatic pathology; such studies often involve the use of human organ donor tissue samples [24, 25] or the establishment of animal models [26, 27]. Hu et al found that the IDEAL IQ sequence can be used for quantitative evaluation of vertebral fat deposition in alloxan-induced diabetic rabbits; however, changes in PFC remain unclear in the context of diabetic rabbits [28]. Importantly, unlike previous MRI techniques used to evaluate visceral fat, the IDEAL-IQ enables adjustment for common biases in the measurement of tissue fat, including T 1 and T 2 * effects, as well as main magnetic field inhomogeneity [29, 30].…”
Section: Discussionmentioning
confidence: 99%
“…China) to generate permeability parameter maps. The Omni‐Kinetics software was designed to generate quantitative parameter maps of DCE and provided not only conventional mean value but also various radiomics features . We applied the extended Tofts linear pharmacokinetic model for DCE‐MRI data analysis.…”
Section: Methodsmentioning
confidence: 99%
“…This technique is often used to quantify hepatic fat in patients with nonalcoholic fatty liver disease . Hu et al reported that the IDEAL‐IQ sequence was useful for quantitative evaluation of changes in vertebral fat deposition in alloxan‐induced diabetic rabbits. Here, we used the IDEAL‐IQ sequence to measure PFF, HFF, and R 2 * values; our results showed that PFF and PFC had a strong positive correlation.…”
Section: Discussionmentioning
confidence: 99%